(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This scientific study was conducted to detect insecticide residues in plums grown in orchards across Uzbekistan during the years 2020–2022. The persistence of insecticides such as organophosphates, pyrethroids, avermectins, emamectins, and neonicotinoids - applied to control pests - was evaluated in the fruit. The analyses were carried out using gas-liquid chromatography (GLC) and high-performance liquid chromatography (HPLC) techniques. According to the results, insecticide residues were generally not detected in the fruit samples, while chlorpyrifos was present at levels below the established maximum residue limits (MRLS). The detection and monitoring of such residues highlight the importance of the rational selection and use of insecticides in ensuring human health protection.